2021
DOI: 10.51253/pafmj.v71i4.4269
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Emptive Effect of Intravenous Paracetamol Versus Intravenous Ketorolac on Post-Operative Pain and Shivering After Septoplasty Under General Anesthesia: A Comparative Study

Abstract: Objective: To observe the pre-emptive effect of intravenous paracetamol versus intravenous ketorolac in preventing postoperative shivering and pain after septoplasty in postoperative care unit. Study Design: Prospective comparative study. Place and Duration of Study: Main Operation Theatre of Frontier Corps Hospital Quetta, from Sep to Dec 2019. Methodology: After ethical committee approval, 90 American Society of Anaesthesiologist (ASA-I patients, aged between 18-45 years, scheduled for sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A low risk of the overall risk of bias for included 9 trials. [11][12][13][14][15][16][17][18] All 9 included trials provided a detailed description of randomization. The Cochrane Handbook for Systematic Reviews of Interventions was used to evaluate the risk of bias of the RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A low risk of the overall risk of bias for included 9 trials. [11][12][13][14][15][16][17][18] All 9 included trials provided a detailed description of randomization. The Cochrane Handbook for Systematic Reviews of Interventions was used to evaluate the risk of bias of the RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…The Cochrane Handbook for Systematic Reviews of Interventions was used to evaluate the risk of bias of the RCTs. Eight studies [11,[13][14][15][16][17][18] were double-blinded. Four trials [11,13,17] reported allocation concealment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of PCM towards the end of the surgery has been reported to have an anti-shivering effect in patients undergoing septoplasty[ 13 ] and during caesarean section under GA.[ 14 ] However, some researchers have also demonstrated PCM's efficacy after anaesthesia induction. [ 1 15 ] Kinjo et al .…”
Section: Discussionmentioning
confidence: 99%